On the analysis of Hopf bifurcation associated with a two-fold zero eigenvalue, Part 2: Nonautonomous system - Moh'd, M; Huseyin, K (Asme-Amer Soc Mechanical Eng, 1999)
This paper extends the bifurcation and stability analysis of the autonomous system considered in Part 1 to the case of a corresponding nonautonomous system. The effect of an external harmonic excitation on the Hopf bifurcation is studied via a modified Intrinsic Harmonic Balancing technique. It is observed that a shift in the critical value of the parameter occurs due to the external excitation. The analysis is carried out with the aid of MAPLE which is also instrumental in verifying the consistency of the approximations conveniently.